2005
DOI: 10.1289/ehp.7198
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and Symptomatic Responses to Low-Level Substances in Individuals with and without Chemical Sensitivities: A Randomized Controlled Blinded Pilot Booth Study

Abstract: We conducted a pilot study using a randomized, single-blind, placebo-controlled exposure among 10 individuals with and 7 without reported chemical sensitivities in a dedicated testing chamber. Objectives of the study were to explore the length of the adaptation period to obtain stable readings, evaluate responses to different substances, and measure the level and type of symptomatic and physiologic reactions to low-level exposures. Reported and observed symptoms, electrodermal response, heart rate, skin temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…20 Studies were categorized by the quality of blinding used: double-or single-blind studies that also included an odorous masking agent to prevent identification of the stimuli (Table I), [21][22][23][24][25][26] double-blind studies without masking (Table II), 11,12,[15][16][17][18][19][27][28][29][30][31][32] single-blind studies without masking (Table III), 13,14,[33][34][35][36][37][38][39][40][41][42][43][44] and open-label studies or studies with unclear blinding (see Table E1 in the Online Repository at www.jacionline.org). 10,[45][46][47] Studies using olfactory masking agents or nose clips Three studies testing 70 chemically sensitive participants incorporated blinding and an olfactory mask and failed to show any significant effects on subjects with MCS after provocation with chemicals.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Studies were categorized by the quality of blinding used: double-or single-blind studies that also included an odorous masking agent to prevent identification of the stimuli (Table I), [21][22][23][24][25][26] double-blind studies without masking (Table II), 11,12,[15][16][17][18][19][27][28][29][30][31][32] single-blind studies without masking (Table III), 13,14,[33][34][35][36][37][38][39][40][41][42][43][44] and open-label studies or studies with unclear blinding (see Table E1 in the Online Repository at www.jacionline.org). 10,[45][46][47] Studies using olfactory masking agents or nose clips Three studies testing 70 chemically sensitive participants incorporated blinding and an olfactory mask and failed to show any significant effects on subjects with MCS after provocation with chemicals.…”
Section: Search Resultsmentioning
confidence: 99%
“…[24][25][26] None of these studies used olfactory masking agents. Participants in these studies showed some response to active provocations, and the authors suggested that participants might have perceived provocations through the eyes.…”
Section: When Is a ''Double-blind'' Study Not Truly Double Blind?mentioning
confidence: 99%
“…Perfume is one of the primary trigger substances for provoking IEI symptoms; therefore, it was unclear whether IEI patients could tolerate an aromatherapy intervention. In addition, IEI patients report a variety of symptoms [6][7][8][9][10][11] , thus for the pilot study, we chose a non-blinded crossover trial in which aromatherapy was given to all of the participants on a randomised crossover basis, despite the limitation of the absence of blinding.…”
Section: Methodsmentioning
confidence: 99%
“…7 Patients with IEI report a variety of symptoms, including fatigue, anxiety, headaches, insomnia, lack of concentration, or depression without physical signs or abnormalities on biomedical tests. [6][7][8][9][10][11] Although the prevalence of IEI varies due to the different definitions of the condition, the estimated number of people suffering from IEI cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The third study, by Joffres et al [16], tested 10 patients who fulfilled the 1999 Consensus Criteria for MCS and seven individuals without chemical sensitivities. None of the patients had a major comorbid disease or history of major depression.…”
Section: Studies With Olfactory Maskingmentioning
confidence: 99%